Embryonic stem cells. Perspectives and problems of their application - Білько, Д.І.; Малишева, С.В.; Будаш, Г.В.; Чапля, О.В.; Білько, Н.М. (Problems of Environmental Biotechnology, 2012)
The application of embryonic stem cells (ESC) is limited by ethic issues concerning the classic method of their derivation. Alternative methods of pluripotent stem cells generation are described; their advantages and disadvantages are evaluated. Pluripotent potential of ESCs is characterized and basic differentiation methods are described. The article also introduces the perspectives of researches focused on multilevel changes typical for genetically abnormal lines of hESC, created with the use of preimplantation genetic diagnosis technique.